Nanodiamond as promising material for bone tissue engineering - Grausova, Lubica; Bacakova, Lucie; Kromka, Alexander; Potocky, Stepan; Vanecek, Milan; Nesladek, Milos; Lisa, Vera (Journal of nanoscience and nanotechnology, 2009)
The adhesion, growth and differentiation of human osteoblast-like MG 63 cells were investigated in cultures grown on nanostructured nanocrystalline diamond (NCD) films with either low surface roughness (rms of 8.2 nm) or hierarchically organized surfaces made of low roughness NCD films deposited on Si surfaces with the original microroughness (rms of 301.0 nm and 7.6 nm, respectively). The NCD films were grown using a microwave plasma-enhanced CVD method in an ellipsoidal cavity reactor. The films were treated in oxygen plasma to enhance the hydrophilic character of the diamond surface (water drop contact angle approx. 20 degrees). The samples were then sterilized by 70% ethanol, inserted into 12-well polystyrene multidishes (diameter 2.2 cm), seeded with human osteoblast-like MG 63 cells (40,000 cells/dish, 10,530 cells/cm2) and incubated in 2 ml of DMEM medium with 10% of fetal bovine serum. On day 3 after seeding, the cell numbers were significantly higher on the nanostructured NCD films (72,020 +/- 6540 cells/cm2) and also on the hierarchically micro- and nanostructured films (60200 +/- 6420 cells/cm2) than on the control polystyrene culture dish (40750 +/- 2,530 cells/cm2). The cells on hierarchically micro- and nanostructured diamond substrates also adhered over a significantly larger area (3730 +/- 180 microm2 compared to 2740 +/- 130 microm2 on polystyrene). The cell viability, measured by a LIVE/DEAD viability/cytotoxicity kit, reached 98% to 100% on both types of NCD films. The XTT test showed that the cells on both nanodiamond layers had significantly higher metabolic activity than those on the control polystyrene dish (approx. 2 to 3 times). Immunofluorescence staining of the cells on both NCD films revealed talin-containing focal adhesion plaques and beta-actin filaments, well apparent particularly at the cell periphery, as well as the presence of considerable amounts of osteocalcin, i.e., a marker of osteogenic cell differentiation. These results suggest that nanocrystalline diamond films give good support for adhesion, growth and differentiation of osteogenic cells and could be used for surface modification of bone implants in order to improve their integration with the surrounding bone tissue.
Keywords: Tissue Engineering; osteokalcin; Cell Line; kosti a kostní tkáň; Culture Media; Actins; Nanostructures; Diamond; Fluorescent Antibody Technique; kultivační média; fluorescenční protilátková technika; osteoblasty; Osteoblasts; nanostruktury; Microscopy, Atomic Force; diamant; aktiny; buněčná adheze; mikroskopie atomárních sil; tkáňové inženýrství; lidé; talin; Humans; buněčné linie; Osteocalcin; Talin; Bone and Bones; Cell Adhesion